PEMBELAJARAN SOSIAL DAN EMOSIONAL (PENGALAMAN PRAKTIS PENDIDIKAN GURU PENGGERAK) - Riswakhyuningsih, Tri; Susiati, Eva; Wulandari; Duryat; Khusnul Fatekhah, Helmi; Kumariyah (Bapelitbang Kabupaten Batang, 2025)
Social and Emotional Learning (SEL) is the 6th module of 10 modules studied in the education of driving teachers. The purpose of the study was to share SEL experiences. The study was conducted using a qualitative descriptive method. Data sources were SEL modules, independent assignments, group assignments, and reflection journals. Data were collected by reviewing modules, exploring the Learning Management System, and documentation. Data analysis was carried out using triangulation techniques. Learning activities used the flow: starting from oneself, concept exploration, collaboration space, contextual meaning, elaboration of understanding, connections between materials, and real action. Starting from oneself, reflection of one's own experience in facing personal crises, the ability to build positive relationships with others and its influence on learning. Concept exploration, exploration of the importance of SEL, the CASEL framework, and implementation of SEL. Collaboration space, discussing and developing social and emotional competence empowerment program initiatives in schools. Contextual demonstration, demonstrating SEL in learning scenarios. Elaboration of understanding, elaborating understanding of SEL based on full awareness through independent learning and mutual cooperation. Connections between materials, making conclusions and connections between SEL with previous modules. Real action, sharing understanding of SEL implementation. Keywords: Leading Teacher, Leading Teacher Education, Social and Emotional Learning